The Relationship between Maternal Characteristics and Parenting Patterns of Feeding for Toddlers in the Special Region of Yogyakarta - Fahna Rahayu l Pratiwi; Silvi Lailatul Mahfida; Neny Fahrun Nisa; Putri Jaya; Annisa Nurdiana Sari; Riska Amelia (GLOBAL HEALTH SCIENCE GROUP, 2024)
There are many factors that influence child nutrition, both internal and external factors. Internal factors such as maternal characteristics are the most influential factors in determining the parenting style applied in feeding children. The purpose of this study was to analyze the influence of maternal characteristics on parenting patterns in feeding toddlers in Yogyakarta. The research method was conducted quantitatively with validity, reliability, and Chi Square test. Data were collected by questionnaire with 211 eligible samples who were mothers aged 17-45 years who had toddlers aged 0-59 months. The validity and reliability test results showed rcount 0.1663 and Cronbach's Alpha 0.9304 so that it was declared valid and reliable. Chi Square test showed no relationship between age, type of work, and level of education on parenting feeding in toddlers in D.I. Yogyarkarta.